(3fhGOQ GdCUhds - (3eMeO Hf Ydj Hf GdMSf Hf HTQ, CHh YHO Gddg, GdMcje GdJQePj , J (B320 (3g` s ((3CHh HcQ Hf Ydi GdCfUGQi GdHgfSi s)
(3ChdgG (B:s
(3bGd eMeO Hf Ydi GdJQePi QMeg Gddg GdCUd GdChd bGd QLd jG QShd Gddg eG feJ GdHGQMI bGd ef Ci TF bGd dOZJfi YbQH s
(3BNQgG (B:s
(3jfJgi HGdCUd GdQGHY hGdKdGKhf hGdeGjg s
(3GdfSNI HgG MhGTs
(3HgG fXGe GdJYbjHIs
(3eUOQ GbJfGA GdCUd (B:s
(3CMeO GdKGdK (B(610(1)) s
Keywords: (3GdJUha hGdBOGH GdTQYjIs